Eco-friendly salt-free reactive dyeing of cotton (muslin) fabric after cationization with amino acid from soya. Issue 20 (December 2016) - Samanta, Ashis Kumar; Kar, Tapas Ranjan; Mukhopadhyay, Asis; Shome, Debashis; Konar, Adwaita
Bleached cotton fabric was chemically modified (cationized)with natural amino acids extract obtained by acid hydrolysis (6N HCL) from soya bean seed waste, adding MgCl2 as an acid donor in the pad-dry-calendaring process to investigate the changes in textile properties and its dyeability with reactive dye in both a conventional alkaline dye bath and salt-free acidic dye bath. This modified cotton incorporates new functional groups producing- NH 3 + in acid bath to obtain cationized cotton, rendering it to eco-friendly salt-free reactive dyeing at acceptable shade depth without much sacrifice of other textile-related properties. Bi-functional high exhaustion-type reactive dye shows better dye uptake than mono-functional cold brand as well as hot brand reactive dye. Moreover, the application of a specific dye fixing agent further improves surface color depth ( K / S ) of the soya-modified cotton fabric. The study of surface morphology of said chemically modified cotton substrate indicates a higher degree of surface deposition, that is, more anchorage of soya extracted amino acids on cotton fabric. Chemical anchorage as per the reaction scheme postulated for such modifications is verified with Fourier transform infrared spectroscopy. Finally, it is revealed that cotton treated with soya extract provides a new route of eco-friendly salt-free reactive dyeing with high exhaustion-type reactive dyes showing much higher dye uptake than the control cotton fabric.